Flexible Crops and Rural Working Youth: From Sugar Cane in Brazil to Palm Oil in Colombia - Robinzon Piñeros Lizarazo (Íconos)
The objective of this paper is to analyze the working conditions of rural young people who stand out among rural workers not only in quantitatively terms but in qualitative terms as well. Young people are the focus of capital interests because their physical and social conditions make them prone to be exploited in the current territorial expansion of the agro-hydro-business of flexible crops in Latin America (such as sugar cane, palm oil, and soy). This situation is exacerbated by the commodity ex-port cycle and the production of agrofuels. In order to analyze this reality, we present data on the age composition of rural young workers involved in the production of sugarcane in the State of São Paulo (Brazil) and palm oil in the departments of Meta and Casanare (Colombia). The methodology of this project is based on the review of databases and interviews with workers and employees of companies that produce the mentioned products